Implementasi Project-Based Learning berbantuan Simurelay pada Mata Pelajaran Instalasi Motor Listrik di Sekolah Menengah Kejuruan - Fival Pratama; Usmeldi Usmeldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
This study aimed to investigate the impact of implementing Project-Based Learning (PjBL) assisted by Simurelay on student learning outcomes in the Electrical Motor Installation course at SMK Negeri 1 Sumatera Barat. The research employed a pre-experimental design with a one-group pretest-posttest approach, involving 30 students from class XI TITL. Data were collected through pretest and posttest assessments, as well as practical skill evaluations. The results indicated a moderate improvement in learning outcomes, with a normalized gain score of 0.4. Additionally, 78% of students achieved the learning mastery criteria (KKTP) after the intervention, while 22% did not meet the standards. The practical skills assessment revealed that most students performed well, with 18 students categorized as